Valve-Preserving Root Reimplantation Combined with Arch Procedure: Optimizing Patient Selection. Issue 3 (May 2022) - Othman, Ahmed A.; Elgharably, Haytham; Vargo, Patrick R.; Ayyat, Kamal S.; Bakaeen, Faisal G.; Johnston, Douglas R.; Tong, Michael Z.; Unai, Shinya; Kalahasti, Vidyasagar; Svensson, Lars G.; Roselli, Eric E.
Objective: Patients with thoracic aortic disease commonly present with concomitant multisegment pathology. We describe the patient population, analyze outcomes, and define the patient selection strategy for valve-preserving aortic root reimplantation (VPARR) combined with the arch procedure.Methods: From 2008 to 2018, 98 patients underwent VPARR combined with the aortic arch procedure (hemi-arch, 50% [ n = 49, limited repair]; total arch, 50% [ n = 49, complete repair] including 39 with elephant trunk). Indications for surgery were aneurysmal disease (61%) and aortic dissection (39%). The median follow-up was 17 months (IQR, 8 to 60 months).Results: There were no operative deaths or paraplegia, and 5 patients underwent re-exploration for bleeding. During follow-up, 2 patients required aortic valve replacement for severe aortic insufficiency at 1 and 5 years, and 4 patients died. In the limited repair group, 1 patient underwent reintervention for aortic arch replacement, whereas 4 patients underwent planned intervention (1 endovascular and 3 open thoracoabdominal aortic repair). In the complete repair group, 23 patients underwent planned intervention (15 endovascular and 8 open thoracoabdominal repair).Conclusions: Single-stage, complete, proximal aortic repair including VPARR combined with total aortic arch replacement is as safe and feasible to perform as limited arch repair and facilitates further intervention in carefully selected patients with diffuse aortic pathology at centers of expertise.